Environmental filters drive functional similarity in disjunct ferruginous outcrops of Eastern Amazonia - Chaves, Viviane Vasconcelos; Sarmento, Priscila; de Castro, Arianne Flexa; Guimarães, José Tasso Felix; de Rezende Cardoso, André Luiz; Tyski, Lourival; da Silva, Rayara do Socorro Souza; Miranda, Thyago Gonçalves; Ramos, Sílvio; Caldeira, Cecílio; Gastauer, Markus (Frontiers in Plant Science, 2026)
Ferruginous outcrops are ecologically formations that host high biodiversity and edaphic endemism. While canga outcrops in Carajás have been the focus of more extensive research, ferruginous outcrops in the Araguaia remain poorly studied, especially with respect to their functional ecology and conservation value. We evaluated the soils, floristic and functional compositions of plant communities on ferruginous outcrops in Carajás and the Araguaia, with the goals of comparing edaphic conditions, floristic compositions, and functional strategies between these disjunct regions and identifying patterns relevant for biodiversity conservation. A total of 129 plots were sampled spanning grassland (GS), shrubland (SB), and woodland (WD) formations. In all plots, soil samples were collected, and plant traits related to resource acquisition (SLA, leaf N, N:P), reproductive strategies (fruit dimensions), and interaction modes (dispersal and pollination syndromes) were measured. Herbaceous and woody communities (trees and treelets with dbh ≥= 3 cm) were analyzed separately. Functional similarity was assessed via community-weighted means and multivariate trait space analyses. Despite exhibiting moderate floristic similarity between regions and edaphic differences, both regions share acidic soils with low phosphorus (P) availability, a condition that imposes similar constraints on resource acquisition. Open formations (GS, SB) in both regions showed functional convergence, indicating similar environmental filters. In contrast, woody communities, especially those in WD, presented pronounced differences in trait composition, reflecting differences in local conditions and ecological history. This study highlights the complementary conservation value of ferruginous outcrops in Carajás and the Araguaia. The functional similarities in open formations suggest that these environments may exhibit ecological strategies associated with similar environmental conditions. Recognizing and protecting these unique environments is essential to ensure their long-term ecological resilience.